Non‐targeted Molecular Characterisation of a Rose Flower Ethyl Acetate Extract Using Ultra‐HPLC with Atmospheric Pressure Photoionisation and Quadrupole Time‐of‐flight MS/MS. Issue 3 (27th January 2015) - Riffault, Ludivine; Colas, Cyril; Destandau, Emilie; Pasquier, Laure; André, Patrice; Elfakir, Claire
Abstract Introduction A non‐targeted approach to characterise the phytochemical composition of the flower organ of an original rose cultivar 'Jardin de Granville'® was developed. Particular attention was paid to the less documented molecular families of intermediate polarity, compared with the polyphenol family (anthocyanins, flavonoids, tannins) and volatile compounds. Objective To develop a molecular fingerprinting method for the rapid qualitative phytochemical characterisation of the rose flower ethyl acetate extract. Material and methods An ultra‐HPLC with atmospheric pressure photoionisation (APPI) and quadrupole time‐of‐flight (QTOF) MS/MS combined with microwave‐assisted extraction was carried out for ethyl acetate extracts as an intermediate polarity extraction solvent in order to obtain the most exhaustive extract containing a large range of molecular families. An optimised methodology based on the coupling of the UHPLC and APPI source with a QTOF analyser was developed to characterise the extracted molecules. Results Sixty‐one compounds were identified in the extract, covering eight molecular families of intermediate polarity ranging from polyphenols to triglycerides. The presence of flavonoids with anti‐oxidant properties and of triterpenoids with potential anti‐inflammatory activity was evidenced and cell‐wall constituents such as fatty acids, glycolipids, sphingolipids and acylated sterol glycosides were characterised. Some chlorophyll derivatives were also detected. Conclusion The method developed is appropriate for fast phytochemical evaluation of rose ethyl acetate extract. It produced accurate mass and MS/MS spectra, which permitted identification of a wide range of compounds of intermediate polarity. Copyright © 2015 John Wiley & Sons, Ltd.